(untitled) (The Review of Diabetic Studies, 2025)
Background: Acute abdominal pain in children presents a significant diagnostic challenge requiring rapid and accurate assessment to prevent morbidity. Ultrasonography (US) is increasingly used as the first-line imaging modality due to its safety, accessibility, and diagnostic precision. Objective: This systematic review aimed to evaluate the diagnostic accuracy, clinical effectiveness, and comparative performance of ultrasound in detecting acute abdominal conditions in children, including appendicitis, intussusception, and other surgical emergencies. Methods: Following PRISMA 2020 guidelines, a comprehensive search of PubMed, Scopus, Embase, Web of Science, and Google Scholar was conducted from inception to December 2025. Ten peer-reviewed studies meeting predefined inclusion criteria were analyzed. Diagnostic parameters (sensitivity, specificity, PPV, NPV, and accuracy) and clinical outcomes were synthesized narratively. Results: Across the ten studies, ultrasound demonstrated a sensitivity range of 58–99.6% and specificity range of 68–100%, with an overall diagnostic accuracy of 90–96%. Studies such as Roberts et al. (2024) and Hajalioghli et al. (2020) reported near-perfect diagnostic accuracy for appendicitis, while Bergmann et al. (2021) confirmed non-inferiority of point-of-care ultrasound (POCUS) compared to radiology-performed US. Ultrasound also enabled alternative diagnoses in up to 100% of negative cases (Lim et al., 2015). Conclusion: Evidence supports ultrasonography as a highly accurate, non-invasive, and indispensable diagnostic tool for pediatric acute abdominal disease, reducing unnecessary surgery and radiation exposure while improving clinical efficiency.